Mahatma Gandhi and Anthropology - Srivastava, Vinay Kumar; Sasikumar, Mundayat (Social Change (New Delhi), 2021)
Anthropology in India has a special relationship with Mohandas Karamchand Gandhi, whom Netaji Subhas Chandra Bose called the ‘Father of the Nation’, and the body of his thoughts that has come to be known as Gandhism. However, with respect to the societies that anthropologists principally study, it is the contribution of Pandit Jawaharlal Nehru that is more often referred. Of all the disciplines, anthropology is the only subject fully committed to an intensive study of tribal societies, the factors of their stability and change. Hopefully, each student of Indian anthropology remembers the Foreword that Pandit Jawaharlal Nehru contributed to the Second Edition of Verrier Elwin’s A Philosophy for NEFA (1958) by heart in which he delineated the five points—euphemistically called Panchsheel (five principles) of tribal policy––that have till date served as its sheet anchor. Since the Fifth Five-Year Plan, a lot of emphasis has been placed on alleviating poverty among the tribal communities, especially for those who have been the victims of deforestation and development-induced displacement and of those who earlier were called Primitive Tribes but are now renamed Particularly Vulnerable Tribal Groups.